IMPLEMENTASI PROGRAM BEBAS SAMPAH (ZERO WASTE) DI KABUPATEN BANDUNG - Mulyana, Asep; Januarharyono, Yudhaswara; Sopandi, Encep (Information Technology and Science (ITScience), 2025)
Abstract The waste problem that generally occurs in the environment around us is a lack of understanding of the importance of disposing of waste where it should be, at several points in the Bandung Regency area is one of the areas where monitoring is not optimal so that it has an impact on various aspects both health, social, culture and others. This writing aims to analyze the waste-free program, find out the factors that hinder the waste-free program and find out the efforts made to overcome the obstacles that occur The results of the study show that the waste clean education corner program has carried out its duties, responsibilities and authorities well, this can be seen from the dimensions of Implementation, 1) Communication, communication established between related human resources 2) Resources, available facilities in zero waste program activities (Zero Waste) 3) Disposition, implementing personnel must be people who have high loyalty 4) Bureaucratic structure, the bureaucracy as the implementer of a policy must support policies that have been decided politically with good coordination. Keywords: Implementation, Zero Waste,